PROSES KREATIF ZAINAL BETA DALAM PENCIPTAAN LUKISAN MEDIA TANAH LIAT - SepBianti Rangga Patriani (Universitas PGRI Adi Buana Surabaya, 2020)
Creative artists are people who cultivate their imagination to always explore art through experimental and trial methods. Experiments carried out by an artist in creating a new work of art are part of an original creative process. As is the case, Zainal Beta is a regional artist in Makassar who develops his artistic creativity by painting using clay media. The purpose of this study was to determine the stages of Zainal Beta's creative process as a clay painter. This research method is described descriptively analysis using the creativity approach. This qualitative research data was obtained through observation, interviews, documentation studies, and literature review. The conclusion of this research is that the stages of the creative process that Zainal Beta went through in the creation of clay painting works originated from inventions accidentally. This discovery motivated Zainal Beta to continue to explore his painting experience using clay media. He continued to develop his creativity in painting using bamboo blades as a painting tool. He used the bamboo slats to make a scratch in painting. Related to the visualization of the object, Zainal Beta clay painting works tend to present the theme of the social and cultural life of the area where he lives, which is depicted in a naturalist and expressive style. The embodiment of the painting object is a representation of various life experiences obtained by Zainal Beta as a clay painter in Makassar.